Research of the Application of Statistical Energy Method in the Prediction of Acoustic Performance of Gearbox - Wang Xin; Zhang Xiaoxu; Zhao Songtao (Jixie chuandong)
Based on the statistical energy analysis theory,a SEA model for a ship gearbox is established and through the theoretical analysis,the three important parameters of statistical energy analysis theory and the bearing dynamic load excitation of gearbox are determined.The high frequency vibration caused by the impact of the gear mesh can be effectively reduced by the gear modification.In order to get the effect of vibration and noise reduction,by using the statistical energy analysis theory,the simulation prediction of each gearbox subsystem vibration velocity and pressure level at a certain distance are carried out respectively in two conditions of gear modification or not.The study shows that,the statistical energy analysis theory can provide an effective method for the analysis of high frequency acoustic performance of gearbox.